Reproductive Outcomes of In Vitro Fertilization and Fresh Embryo Transfer in Infertile Women With Adenomyosis: A Retrospective Cohort Study - Liang, Tingting; Zhang, Wen; Pan, Ningning; Han, Bing; Li, Rong; Ma, Caihong (Frontiers in Endocrinology, 2022)
Background Adenomyosis is commonly encountered in infertile women; however, it is still unclear whether adenomyosis has a detrimental effect on in vitro fertilization and embryo transfer (IVF-ET) outcomes. Method We enrolled 1146 patients with adenomyosis and 1146 frequency-matched control women in a 1:1 ratio based on age, BMI, and basal follicle-stimulating hormone (FSH) level. After controlling for other factors, the rates of clinical pregnancy, miscarriage, live birth, and obstetric complications were compared between two groups. Results There was no significant difference in clinical pregnancy rate between the two groups (38.1% vs. 41.6%; P=0.088). The implantation rate (25.6% versus 28.6%, P=0.027) and live birth rate (26% versus 31.5%, P=0.004) were significantly lower in the women with adenomyosis than in the controls. The miscarriage rate in the adenomyosis group was higher than that in the control group (29.1% versus 17.2%, P=0.001). After adjusting for confounding factors, multivariate analysis showed the clinical pregnancy rate was not statistically different between the two groups (OR: 0.852, P=0.070). In the adenomyosis group, the rate of miscarriage(OR: 1.877, P=0.000), placenta previa (OR: 2.996, P=0.042)and preeclampsia (OR: 2.287, P=0.042)were increased significantly, while live birth rate (OR: 0.541, P=0.000) was reduced significantly than control group. Conclusion Adenomyosis has negative effect on IVF-ET outcomes in which miscarriage risk increased, live birth rate reduced and obstetric complications increased.